Принцип динамічного підстроювання як спосіб підвищення якості тонколистового розділового штампування - Мірзак, В. Я.; Боков, В. М.; Mirzak, V.; Bokov, V. (КНТУ, 2016)
Запропоновано та досліджено принцип динамічного підстроювання як спосіб підвищення якості тонколистового розділового штампування за рахунок розвантаження напрямних вузлів від радіальних зусиль та суттєвого зменшення деформації деталей штампа. Розроблено та випробувано гаму оригінальних механічних компенсаторів похибок системи «прес-штамп», які використовуються як пристрої для реалізації принципу динамічного підстроювання. The purpose of the research is thin-sheet dividing stamping quality increase due to the application of dynamic adjustment principle. The quality of thin-sheet dividing stamping is determined first of all by the “press-stamp” system state, namely it depends on the loaded stamp detail deformation degree, as the given system is a source of nearly 60 per cent of errors which influence the loss of quality. The main idea of the paper is the possibility to significantly improve the quality increase of thin-sheet dividing stamping due to the application of the offered principle of dynamic adjustment. Stamping is done with dynamic adjustment of the “press-stamp” system in the direction of the coincidence of the press technological effort application axis with the axis that goes through stamp pressure centre. The quality increase is reached due to unloading the guide units of radial efforts and significant deformation decrease of stamp parts. The offered mechanical compensators that realize the given principle demonstrated significant improvement of stamping quality (lifting up decrease, dimension deviation scale, etc).
The principle of dynamic adjustment as a means of thin-sheet dividing stamping quality increase
Keywords: динамічне підстроювання; механічний компенсатор; якість розділового штампування; тонколистове штампування; dynamic adjustment; mechanical compensator; dividing stamping quality; thin-sheet stamping